Subnational variation in policy implementation: the case of Nigerian land governance reform - Resnick, Danielle; Okumo, Austen (International Food Policy Research Institute, 2017)
When and why do policymakers implement land governance reforms? We address this question by focusing on differential implementation of Systematic Land Tenure Regularization (SLTR) across six states in Nigeria. Although improved land governance has many long-term benefits, including developed property and housing markets, increased agricultural investment, and an expanded source of revenue, the short-term outcomes are less visible to citizens. In theory, this would create low political incentives for implementation among policymakers. In practice, we observe higher levels of implementation in some states compared to others despite almost universally low public demand for SLTR. To explain this puzzle, we use a structured comparative analysis that draws on interviews with more than 90 federal and state-level stakeholders in Cross River, Jigawa, Kaduna, Kano, Katsina, and Ondo states. We find that the collective presence of bureaucratic autonomy, diversity of donor funding, and continuity in state government administrations are more likely to explain where SLTR implementation has progressed the most.